2020
DOI: 10.3322/caac.21627
|View full text |Cite
|
Sign up to set email alerts
|

Hematology and oncology clinical care during the coronavirus disease 2019 pandemic

Abstract: New York City has been at the epicenter of the coronavirus disease 2019 (COVID-19) pandemic that has already infected over a million people and resulted in more than 70,000 deaths as of early May 2020 in the United States alone. This rapid and enormous influx of patients into the health care system has had profound effects on all aspects of health care, including the care of patients with cancer. In this report, the authors highlight the transformation they underwent within the Division of Hematology and Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 8 publications
0
28
0
1
Order By: Relevance
“… 1 To continue care for patients while also minimizing exposure to health care staff, the Weill Cornell Medicine Division of Hematology and Medical Oncology created separate units for patients with confirmed COVID-19, patients with symptomatic but unconfirmed COVID-19, and asymptomatic patients with no known high-risk COVID-19 exposures. 2 Patients were contacted prior to their appointment and triaged based on their COVID-19 risk status. To understand the success of our clinical screening and triaging procedures, we implemented a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing protocol in asymptomatic patients who required cancer care across the Division of Hematology and Medical Oncology.…”
Section: Introductionmentioning
confidence: 99%
“… 1 To continue care for patients while also minimizing exposure to health care staff, the Weill Cornell Medicine Division of Hematology and Medical Oncology created separate units for patients with confirmed COVID-19, patients with symptomatic but unconfirmed COVID-19, and asymptomatic patients with no known high-risk COVID-19 exposures. 2 Patients were contacted prior to their appointment and triaged based on their COVID-19 risk status. To understand the success of our clinical screening and triaging procedures, we implemented a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing protocol in asymptomatic patients who required cancer care across the Division of Hematology and Medical Oncology.…”
Section: Introductionmentioning
confidence: 99%
“…The severe acute respiratory virus coronavirus-2 (SARS-CoV-2) pandemic caused major changes also in health care support for patients with cancer worldwide (Maringe et al 2020;Shah et al 2019;Sud et al 2020;van de Haar et al Jun Ma and Xiaojun Huang have contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…The severe acute respiratory virus coronavirus-2 (SARS-CoV-2) pandemic caused major changes also in health care support for patients with cancer worldwide (Maringe et al 2020 ; Shah et al 2019 ; Sud et al 2020 ; van de Haar et al 2020 ). Recommendations from many professional societies suggest an individualized decision-making (Al-Shamsi et al 2020 ; Di Ciaccio et al 2020 ; ESMO 2020 ; Ismael et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We started from scratch and physical visits were restricted to emergency or daycare only. A study from New York hospital reported that around half of their patients who could not be attended on site were contacted by telemedicine visits in early 2020 [7]. In a global survey about oncology practice during COVID-19 pandemic, over 80% participants were using telemedicine in some form or another [8].…”
Section: Discussionmentioning
confidence: 99%